2015
DOI: 10.1097/fjc.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

First-in-man Study With Inclacumab, a Human Monoclonal Antibody Against P-selectin

Abstract: Abstract:Inclacumab, a novel monoclonal antibody against P-selectin in development for the treatment and prevention of atherosclerotic cardiovascular diseases, was administered in an ascending single-dose study as intravenous infusion to evaluate safety, pharmacokinetics, and pharmacodynamics. Fifty-six healthy subjects were enrolled in this randomized, double-blind placebo-controlled study. Each dose level (0.03–20 mg/kg) was investigated in separate groups of 8 subjects (6 on inclacumab, 2 on placebo). Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Herein we make this role tangible in patients with atherosclerosis and related cardiovascular diseases. Blocking P-selectin may represent a more feasible approach to inhibit platelet-monocyte interactions and to reduce atherosclerosis, as shown by several animal studies (60,61) and two recent clinical trials which tested the newly developed anti-P-selectin antibody inclacumab (62,63). In addition, platelet-vWF interactions can be blocked by specific antibodies targeting vWF GpIb (caplacizumab) and platelet GpIb receptor (anfibatide), which have recently been tested in phase I and phase II clinical trials with very promising results (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Herein we make this role tangible in patients with atherosclerosis and related cardiovascular diseases. Blocking P-selectin may represent a more feasible approach to inhibit platelet-monocyte interactions and to reduce atherosclerosis, as shown by several animal studies (60,61) and two recent clinical trials which tested the newly developed anti-P-selectin antibody inclacumab (62,63). In addition, platelet-vWF interactions can be blocked by specific antibodies targeting vWF GpIb (caplacizumab) and platelet GpIb receptor (anfibatide), which have recently been tested in phase I and phase II clinical trials with very promising results (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal models demonstrated that inhibition of P-selectin can impact the development of atherosclerosis, fibrin deposition and thrombus growth [21,[57][58][59]. In humans, high levels of sP-selectin are also found in cardiovascular disease, atrial fibrillation and diabetes [60], and may be predictive of future adverse cardiovascular events [21,61,62].…”
Section: P-selectinmentioning
confidence: 99%
“…inflammatory and antithrombotic platelet-dependent processes that are instrumental in atherogenesis, a P-selectin blocking monoclonal antibody (inclacumab) has been developed and tested in humans with NSTEMI, which resulted in decreased peri-interventional myocardial damage. 26 As a side note, P-selectin expression is enhanced in platelets and endothelial cells in patients with sickle cell disease contributing to the risk of vaso-occlusive crises. A humanized monoclonal antibody, crizanlizumab, has been shown in the SUSTAIN trial to protect patients with sickle cell disease from vaso-occlusive crises and has recently been approved by the Food and Drug Administration for this indication.…”
Section: P-selectinmentioning
confidence: 99%